Teacher Professional Development Program in Indonesian Public Elementary Schools: Developing a Mini Course in Basic EYL (English for Young Learner) Teaching Skill - Al Ikhwan Fadqur Rohqim (J-SHMIC : Journal of English for Academic, 2020)
The teaching of English in Elementary Schools in Indonesia have been conducted for decades, but based on literature review and preliminary study, most of the teachers teaching English in Public Elementary Schools, both in the regular local content subject or English extracurricular activities have inadequate English and English teaching skills. In-service training was proposed due to the teachers’ time availability. The training activities will be conducted after school hours and taken place in their schools. The development of the training employs a research and development research method comprising the preliminary study, class observations, interview, the development of materials, instructional media and evaluation that will be validated by the experts. After the expert validation stage, the products which have been revised based on the experts’ suggestions are then applied in the field validation. The last stage is the revision of the products based on field validation. This product is projected to be an example of a teacher professional development program for teachers teaching English in Elementary School.